Analysis of Time Utilization Pattern of Rural Women Engaged in Livestock Rearing as Compared to Men Folk - Chanoria, A.; Kumar, Pranav; Ahmed , R.; Shah, M. (International Journal of Livestock Research, 2019)
Rural women in our country share abundant responsibilities both at household and farm level and perform a wide spectrum of duties but their role in livestock management continues to be underestimated at large. In J&K state no data regarding their role in livestock management was available from any area or region, therefore analysis of time utilization pattern of rural women engaged in livestock rearing as compared to men folk in Kathua district of J&K state was undertaken. The data was collected from four blocks of Kathua district taking 120 female respondents as well as their male counterparts engaged in livestock rearing. Thus, 240 respondents in all interviewed. In socio-economic profile context of rural women, it was found that majority of the respondents were of the middle aged, having poor education, marginal land holding, engaged in mixed type of family occupation and moving towards to nuclear family as per the normal trends of Indian family system. The time utilization pattern of rural women was significantly higher as compared to their male counterpart in general livestock related activities but when it came to marketing, credit, health and reproductive management of animals, rural men were more prominently engaged and had given major time in all such activities.